Cyclical changes of space : the phenomena of space changes in historic-religious Kampung Luar Batang, Jakarta, Indonesia / Popi Puspitasari, Achmad Djunaedi and Heddy Shri Ahimsa Putra - Djunaedi, Achmad; Ahimsa Putra, Heddy Shri; Puspitasari, Popi (Faculty of Architecture, Planning and Surveying, 2012)
Kampung Luar Batang is a modern-traditional urban settlement occupied by a heterogeneous community with hybrid culture, at the proximity of an urban pilgrimage center - a maqom (sacred tomb).